Analysis of Costs and Revenue of Arabic Coffee Farming and its Sales System: Case Study: Situmeang Habinsaran Village, Sipoholon District, North Tapanuli Regency, North Sumatra Province - Hutapea, Kenal P.; Ginting, Nina Maksimiliana; Harefa, Niasti Nur Adil (Journal of Agriculture, 2024)
This research aims to determine the production costs and revenues of Arabica coffee farming in the research area to determine the net income and income of Arabica coffee farming families in the research area; to determine the feasibility level of Arabica coffee farming in the research area; to find out how the Arabica coffee sales system is in the research area. Determining the research area was carried out purposively. The sampling method is a simple random sampling method with a sample size of 30 farmers. The data analysis methods used are primary data and secondary data. The research results obtained several conclusions: The total cost of Arabica coffee farming in the research area for one year is IDR 24,747,244.44/Farmer or IDR 38,969,822.66/Ha. Revenue from coffee farmingamounting to IDR 102,758,553.33/Farmer or IDR 160,581,337.78/Ha; The net income of Arabica coffee farming for one year is IDR.78,011,308.89/Farmer or Rp.118,834,031.78/Ha. The income of an Arabica coffee farming family for one year is IDR 98,325,542.22/Farmer or IDR 152,317,561.41/Ha; The RCR value for coffee farming in the research area is 4.27 or RCR > 1. This shows that coffee farming is still feasible to cultivate or develop in the research area. The Arabica coffee sales system in the research area is that Arabica coffee farmers sell their harvest to regional collectors, market it to district collectors, and then sell it to provincial collectors.